CORRELATION BETWEEN MAXIMUM INSPIRATORY PRESSURE (MIP) AND PEAK OXYGEN UPTAKE (VO2 PEAK) IN FEMALE PROFESSIONAL SOCCER ATHLETES - Floriano, Rafael Santiago; Areias, Guilherme De Souza; Silva Reis, Michel (Journal of Respiratory and CardioVascular Physical Therapy, 2020)
Background: Ventilatory muscle training (VMT) has been described as a strategy to improve ventilatory and peripheral muscle strength and endurance in athletes of different modalities. However, the mechanisms involved in this process are not fully known. Oxygen uptake (VO2) is the gold standard variable for assessing functional capacity. Oxygen (O2) to be consumed by the peripheral muscles must pass through the cardiorespiratory system. In this rationale, it seems logical that the stronger the inspiration muscles, the higher the VO2. This work has shown that this may not be as deterministic as it sounds. Objective: To evaluate the correlation between inspiratory muscle strength through maximum inspiratory pressure (MIP) and peak oxygen uptake (VO2 peak) in female professional soccer athletes. Study Design: Prospective and cross-sectional study. Methods: 16 professional soccer players, female and aged between 18 and 40 years (26 ± 4.3), underwent measurement of maximum inspiratory pressure (MIP -120.7 ± 16.9) and performed the cardiopulmonary exercise test (TECP) in a treadmill, where the ventilatory and metabolic variables were measured. One of them was the VO2 peak (44.30 ± 5.9). The volunteers were assessed on the same day and time as follows: (i) assessment of inspiratory muscle strength; and, (ii) incremental cardiopulmonary exercise test up to maximum tolerance. The data were analyzed using the SPSS® version 13.0 statistical program, and Pearson's correlation was made between MIP and VO2peak. Importance of the Study: This study can reveal what kind of correlation exists between these important markers, helping in the development of new strategies for improving performance in sport. Results: The volunteers presented a MIP of -120.7 ± 16.9, and in the TECP on a treadmill, they obtained a VO2peak of 44.30 ± 5.9. The statistical analysis showed an inverse association with r = -0.14 and p = 0.612 between MIP and VO2peak. Conclusion: There was an inversely proportional correlation between MIP and VO2peak; thus, this result leads us to believe that inspiratory muscle strength does not seem to influence VO2peak directly.